Mycoplasma genitalium in medical practice: silent as Chlamydia, but with greater potential for aggressiveness - Carvalho, Newton Sergio de; Palú, Gabrielle (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Mycoplasmas belong to the Mollicutes classification. The first species was discovered in 1898 by Nocaard & Roux in a case of pneumonia. In this classification four species have a higher impact on a bovine pneumonia case. The Ureaplasma genus focusing on the Urealiticum and Parvum species may be related with problems during pregnancy or even with perinatal impact(1), whereas the Mycoplasmas genus represented by the hominis and the genitalium species are more related to disturbances in the genitals, but can also have an impact on pregnancy(1). Among these, Mycoplasma genitalium (MG) stands out regarding its pathogenicity, especially the growing resistance to antibiotics as shown in recent studies(2,3). [...]